Clinical efficacy of linezolid in the treatment of tuberculous meningitis: a retrospective analysis and literature review - Zhen-Tao Fei; Wei Huang; Dan-Ping Zhou; Yang Yang; Ping Liu; Ning Gan; Ping-Ping He; Dan Ye; Hua-Rui Liu; Xu-Hui Liu; Lu Xia (BMC Infectious Diseases)
Highlights Retrospective study evaluating linezolid in 99 TBM patients. Linezolid significantly reduced CSF protein levels, especially in critically ill patients. Similar adverse event rates between groups. Relevant literature reviews were reviewed.